Pathophysiology of stroke rehabilitation: temporal aspects of neuro-functional recovery - Kreisel, Stefan H.; Bäzner, Hansjörg; Hennerici, Michael G. (Cerebrovascular diseases, 2006)
Stroke almost always causes an impairment of motor activity and function. Clinical recovery, though usually incomplete, is often highly dynamic and reflects the ability of the neuronal network to adapt. Mechanisms that underlie neuro-functional plasticity are now beginning to be understood. Albeit the enormous efforts undertaken to support the natural course of re-convalescence through rehabilitation, little has been done to relate possible effects of these therapeutic approaches to mechanisms of adaptive pathophysiology. The review presented here focuses on these mechanisms during the course of recovery post stroke. Next to an unmasking of latent network representations, other adaptive processes, such as excitatory metabolic stress, an imbalance in activating and inhibiting transmission, leading to salient hyperexcitability or mechanisms that consolidate novel connections prime the system's plastic capabilities. These pathophysiological processes potentially interact with rehabilitative interventions. They therefore form the foundation of positive, but possibly also negative recuperation under therapy.
Published online: November 8, 2005
Gesehen am 09.05.2022